COVID-19 rapid evidence profile #12: What insights from the available evidence and jurisdictional scans can inform who should be tested for COVID-19 and how frequently, where, by whom and with what follow-up actions should they be tested? - Wilson, MG; Waddell, K; Gauvin, François-Pierre; Mansilla, C; Moat, KA; Wang, Q; Voorheis, P; Bhuiya, AR; Ahmad, A; Lavis, JN (My University, 2020)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about insights from the available evidence and jurisdictional scans that can inform who should be tested for COVID-19 and how frequently, where, by whom and with what follow-up actions they should be tested in response to a decision-maker’s request.
Keywords: evidence; jurisdictional; testing; COVID-19; frequency; follow-up